Skew Surges - Marta Marcos; Philip Woodworth (Zenodo, 2022)
Supplementary data set of the paper: Marcos, M. and Woodworth, P.L. 2017. Spatio-temporal changes in extreme sea levels along the coasts of the North Atlantic and the Gulf of Mexico. Journal of Geophysical Research Oceans, 122, doi:10.1002/2017JC013065. The file contains the skew surges computed for all tide gauge records in GESLA2 data base, as described in the above publication.